The role of the state in creating a green economy - Institute of Economic Research, Torun; Szyja, Paulina (Torun, 2015)
"Starting from the crisis on the real economy in 2008 it has been developed an intense discussion, supported by a number of declarations on the global scale, about the need for changes in the economy. A huge impact on this state of affairs was the analysis of the causes and effects of the economic downturn and the challenges of the future. As a result, some states have taken action to remedy the situation. Many of them were aimed at structural changes in production, consumption and environmental friendly investment. At the same time gained in importance the concept of "low carbon economy" and "green economy". The aim of this paper is to present the role of the state in the economy in terms of creating conditions for a green economy. The thesis of publication is: implementation of structural changes connected with creating a green economy requires the involvement of the state."